2007
DOI: 10.1309/pftpll4hck2d1erk
|View full text |Cite
|
Sign up to set email alerts
|

Familial B-Cell Chronic Lymphocytic Leukemia

Abstract: B-cell chronic lymphocytic leukemia (B-CLL) is a heterogeneous disease that may exhibit familial clustering. We examined the cytogenetic, immunophenotypic, and VH gene usage characteristics of a family with B-CLL affecting 7 members in 3 generations. Interphase fluorescence in situ hybridization studies identified an acquired deletion of chromosome 13q14 in the leukemic cells of 6 affected members, accompanied by deletion 14q32 or trisomy 12 in 2 cases. VH gene analysis demonstrated clonal rearrangements of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…Cytogenetic and immunophenotypic results of familial and sporadic B-CLL patients were similar to each other. Some other studies analyzing familial B-CLL cases have also suggested similar findings (54, 55). …”
Section: Discussionsupporting
confidence: 75%
“…Cytogenetic and immunophenotypic results of familial and sporadic B-CLL patients were similar to each other. Some other studies analyzing familial B-CLL cases have also suggested similar findings (54, 55). …”
Section: Discussionsupporting
confidence: 75%
“…Bi-allelic or concomitant monoallelic/biallelic deletions are detected in up to 1/3 of sporadic cases with 13q14 loss and have also been reported in the setting of familial occurence. 5 , 6 High density mapping of familial cases has revealed a commonly shared haplotype in a locus near 13q14 that may comprise susceptibility genes for the pathogenesis of CLL. Interestingly, 85% of familial members sharing this region have deletions in 13q14.…”
mentioning
confidence: 99%